Ornamentality, rhythm and repetition of prose: G. G. Bagautdinova: “Poetics of I. A. Goncharov’s non-novel prose”. Yoshkar-Ola, Mari State University, 2024, pp. 296. ISBN: 978-5-907622-93-7 - Németh, Katalin (Slavica, 2025)
This paper examines the relevance of G. G. Bagautdinova's book Poetics of I. A. Goncharov’s non-novel prose, which is undeniable and is due to a range of reasons indicated in the paper. First, it reviews the holistic understanding of I. A. Goncharov's creative path in his so-called "essay" works. The scholarly novelty of the monograph is analyzed point by point parallel to the constructed structure of the book. In this regard, the following so far little-studied and unexplored aspects are examined: the framework text, the cumulation of folklorism, "ornamental prose", the rhythm of prose, and the poetics of repetition. The unconditional discoveries of this work are the conclusions in terms of the objective results achieved.